92 males buy tickets so
200-92=108
so 108 females buy tickets
30 males buy business and a total of 44 people (female and male) but business so 44-30=14
14 females buy business
108-14(business ticket) = 94 females left.
62 of those 94 females buy economy tickets
so therefore 94-62=32. 32 females left over
14 females = business
62 females = economy
14 + 62 = 76
108 - 76 = 32
32 remaining females buy premium
it says a total of 60 people buy premium so 60 - 32 = 28
so 28 males buy premium
hope this helped
Answer:
![y = -0.1x^2 + 250 ft](https://tex.z-dn.net/?f=y%20%3D%20-0.1x%5E2%20%2B%20250%20ft)
Step-by-step explanation:
Because this quadratic equation would have the curve-down form of:
![y = -ax^2 + b](https://tex.z-dn.net/?f=y%20%3D%20-ax%5E2%20%2B%20b)
where a and b are positive coefficient.
If we let the peak (250 ft) of the curve be at x = 0. Then
![y = -a0^2 + b = 250](https://tex.z-dn.net/?f=y%20%3D%20-a0%5E2%20%2B%20b%20%3D%20250)
![b = 250](https://tex.z-dn.net/?f=b%20%3D%20250)
Also at the begins and ends, thats where y = 0, the 2 points are separated by 100 ft. So let the begin at -50 ft and the end at 50ft. We have
![-a(\pm 50)^2 + 250 = 0](https://tex.z-dn.net/?f=-a%28%5Cpm%2050%29%5E2%20%2B%20250%20%3D%200)
![-a2500 = -250](https://tex.z-dn.net/?f=-a2500%20%3D%20-250)
![a = 250/2500 = 0.1](https://tex.z-dn.net/?f=a%20%3D%20250%2F2500%20%3D%200.1)
Therefore, the model quadratic equation of our path would be
![y = -0.1x^2 + 250 ft](https://tex.z-dn.net/?f=y%20%3D%20-0.1x%5E2%20%2B%20250%20ft)
Answer: 50.2 liters
Step-by-step explanation:
11 liters = 50km
Z liters = 228km
To get the value of Z, cross multiply
228 x 11 = Z x 50
2508 = 50z
Divide both sides by 50
2508/50 = 50z/50
50.16 = z
50.16 has two decimal places, so convert to 1 decimal place by approximation
50.16 = 50.2
Thus, 50.2 liters will be enough for 228km
Answer:
x=90 y=58 z=32
Step-by-step explanation:
I don't know how to explain it but yea
Answer:
1) b 2) b
Step-by-step explanation:
1) Both expressions have (x+6). Rearrange them and you'll have one expression as (x+6) and the other as (5ab-4).
2) (4b - 7x)(a + b) factors to be 4ba + 8b - 7ax - 14x, which can be rearranged to 4ab - 7ax + 8b - 14x